EFFECTS OF FERMENTED Hibiscus sabdariffa SEED BASED DIETS ON HAEMATOLOGICAL PARAMETERS OF Clarias gariepinus (BURCHELL, 1822) FINGERLINGS - USMAN, U; HASSAN, M. Z.; SHETTIMA, H. M.; INUSA, M.; DIYAWARE, M. Y. (Nigerian Journal of Fisheries, 2022)
A Twenty-one week experiment was conducted to evaluate changes in the blood indices of Clarias gariepinus fingerlings fed with five Iso-nitrogenous diets with 40 % crude proteins were formulated by incorporating 0, 25, 50, 75, and 100% of fermented Hibiscus sabdariffa seed meal as a replacement for soya bean meal. A total of 150 fingerlings of C. gariepinus (weight 4.0 - 4.4g) were randomly allocated into fifteen rectangular net hapa (1 m × 1 m × 1.2 m) at 10 fish per hapa installed in a polyethene lined pond (7 x 5 x 1.2 m) and fed twice daily at 5% body weight. Fish blood samples were collected to determine blood indices. The results showed that fish fed 75% FHSSM based diet had the best PCV (37.67%) while those on 25% FHSSM -based diet had the least PCV (27.00%). There were elevated values of Hb (8.93 to 13.60g/dL), RBC (2.28-2.57 x10⁶/mm³), WBC (4.15–4.38 x10³/mm³), MCV (11.72 – 14.71fl), MCH (52.81-39.60) and MCHC (34.33–47.83) for the entire treatments. Fish fed 75% FHSSM inclusion had the highest Hb (13.60g/dL), RBC (2.57 x10⁶/mm³), WBC (4.38 x10³/mm³), MCV (14.71), MCH (47.83), Lymphocytes (76.00%) and neutrophils (42.33%). The haematological parameters revealed that there was no significant difference (P > 0.05) among the treatments in most of the parameters. All the indices fell within recommended ranges for healthy fish.